Anti-tumor Effect of Rhaponticum uniflorum Ethyl Acetate Extract by Regulation of Peroxiredoxin1 and Epithelial-to-Mesenchymal Transition in Oral Cancer - Chen, Hui; Wang, Chunxiao; Qi, Moci; Ge, Lihua; Tian, Zhenchuan; Li, Jinhua; Zhang, Min; Wang, Min; Huang, Linfang; Tang, Xiaofei (Frontiers in Pharmacology, 2017)
Abstract Objective: To explore whether Rhaponticum uniflorum (R. uniflorum) had anti-tumor effects in oral cancer and investigate the molecular mechanisms involved in these anti-tumor effects. Methods: Chemical compositions of R. uniflorum ethyl acetate (RUEA) extracts were detected by ultra-performance liquid chromatography-Q/time-of-flight mass spectrometry (UPLC-Q/TOF-MS), followed by pharmacology-based network prediction analysis. The effects of RUEA extracts on proliferation, apoptosis, migration, and invasion ability of human oral squamous cell carcinoma (OSCC) cell line SCC15 were evaluated by CCK8 assay, Annexin V- fluorescein isothiocyanate/propidium iodide staining, wound healing assay, and Matrigel invasion assay, respectively. The mRNA and protein expression of peroxiredoxin1 (Prx1), the epithelial-to-mesenchymal transition (EMT) marker E-cadherin, vimentin, and Snail were determined by quantitative real-time reverse transcription polymerase chain reaction and western blotting. A mouse xenograft model of SCC15 cells was established to further evaluate the effect of RUEA extracts in vivo. Immunohistochemical assessment of Ki67 and terminal deoxynucleotidyl transferase dUTP nick end labeling staining of apoptotic cells were performed on the tumor tissues to assess the effects of RUEA extracts on proliferation and apoptosis. Results: Fourteen compounds were identified from RUEA extracts by UPLC-Q/TOF-MS. The pharmacology-based network prediction analysis showed that Prx1 could be a potential binder of RUEA extracts. In SCC15 cells, RUEA extracts inhibited cell viability, induced apoptosis, and suppressed cell invasion and migration in a concentration-dependent manner. After treatment with RUEA extracts, the mRNA and protein expression of E-cadherin increased, whereas those of Prx1, vimentin, and Snail decreased. RUEA extracts also affected the EMT program and suppressed cell invasion and migration in Prx1 knockdown SCC15 cells. In an OSCC mouse xenograft model, RUEA extracts (25 mg/kg and 250 mg/kg) significantly inhibited the growth of tumors. Compared with the control group, Ki67 expression was reduced and apoptosis rates were elevated in the transplanted tumors treated with RUEA extracts. RUEA extracts increased the expression of E-cadherin and decreased the expression of Prx1, vimentin, and Snail in vivo. Conclusions: RUEA extracts inhibited tumor growth and invasion by reducing Prx1 expression and suppressing the EMT process in OSCC. RUEA extracts may be a potential candidate for OSCC treatment.